'The Man Within': Adam Smith on Moral Autonomy and Religious Sentiments. Issue 1 (March 2017) - Chen, Jeng-Guo S.
Abstract : This essay analyses the ethical importance and religious implications of 'the man within' in Adam Smith's moral philosophy. Not introduced until the second edition of Theory of Moral Sentiments, 'the man within' appears as the internalization of the impartial spectator. With the invention of the man within, Smith was able to explain how moral agents pursue virtues and behave morally beyond immediate and quotidian concerns with either praises or blames from society. Having complied with the general dictates of the impartial spectator with conscience, humans become morally autonomous individuals whose moral judgements are derived from constant dialogues with the man within in an ethical microcosm within their breasts. The man within possesses a transcendent nature that preempts social judgements. Because of that transcendent nature, Smith also denominated the man within as 'the substitute of Deity'. This essay also argues that even conscientious and virtuous individuals can be wronged and misjudged by society. To Smith, religious sentiments were most likely generated among the morally autonomous, innocent people. Afflicted with devastating distranquility of the mind caused by misjudgments of society, the innocent can only find comfort in the hope for the afterlife. The essay concludes that Smith's religious view in this particular regard goes hand in hand with his great concern with justice prevailing in his writings of political economy, government and ethics.